PENINGKATAN ADAPTASI COVID-19 DAN MODERASI BERAGAMA - dwi adityo, rayno (JRCE (Journal of Research on Community Engagement), 2021)
The Covid-19 pandemic does not seem to be over yet, the problems that arise are so many as a result of the epidemic, starting from the problem of the decline in the economic sector, limited community mobility so that the government always encourages to implement health protocols, starting from maintaining distance, avoiding crowds, always washing hands , carrying a hand sanitizer, and wearing a mask when traveling, are not only a pandemic problem but also the penetration of destructive religious ideas that tends to be radical so that it is again necessary to spread a moderate religious perspective. Through the Ministry of Religion of the Republic of Indonesia, the socialization of religious moderation has begun again. The purpose of carrying out this community service research is first, as a form of embodiment of the tri darma of higher education in the field of community service; second, so that people can improve their adaptation to the environment and conditions that are currently happening. The methods used are lectures, providing information, simulations and training within the framework of the Paticipatory Rural Apprasial. The results achieved were the implementation of socialization in the context of preventing Covid-19 by making posters, flyers, spandung, giving advice and education. In the religious moderation program, namely by inserting messages of peace in religion in educational institutions, TPQ, and Islamic boarding schools, but some are using virtual platforms. Economic and community empowerment program by reviving one of the local tourist sites in Dhompo village, Pasuruan Regency. Community needs program by producing an information technology-based village application product. The conclusion is that the more people can improve their adaptation in pandemic conditions, the hope is that they can improve safety and also change their habit patterns to stay productive.